Drug-induced seizures in children and adolescents presenting for emergency care: Current and emerging trends. (September 2013) - Finkelstein, Y.; Hutson, J. R.; Freedman, S. B.; Wax, P.; Brent, J.; ,
Abstract Context. Seizures may be the presenting manifestation of acute poisoning in children. Knowledge of the etiologic agent, or likely drug-class exposure, is crucial to minimize morbidity and optimize care. Objectives. To describe the agents most commonly responsible for pediatric drug-induced seizures, whose evaluation included a medical toxicology consultation in the United States. Methods. Using the 37 participating sites of the Toxicology Investigators Consortium (ToxIC) Case Registry, a cross-country surveillance tool, we conducted an observational study of a prospectively collected cohort. We identified all pediatric (younger than 18 years) reports originating from an Emergency Department (ED) which included a chemical or drug-induced seizure, and required a medical toxicology consultation between April 1, 2010 and March 31, 2012. Results. We identified 142 pediatric drug-induced seizure cases (56% male), which represent nearly 5% of pediatric cases requiring bedside consultation by medical toxicologists. One-hundred and seven cases (75%) occurred in children aged 13–18 years, and 86 (61%) resulted from intentional ingestions. Antidepressants were the most commonly identified agents ingested (n = 61; 42%), of which bupropion was the leading drug (n = 30; 50% of antidepressants), followed by anticholinergics/antihistamines (n = 31; 22%). All antidepressant-induced seizures in teenagers were intentional and represented self-harm behavior. Sympathomimetic agents, including street drugs, represent the most common agents in children younger than 2 years (n = 4/19). Conclusion. Antidepressants, and specifically bupropion, are presently the most common medications responsible for pediatric drug-induced seizures requiring medical toxicology consultation in the United States. In teenagers presenting with new-onset seizures of unknown etiology, the possibility of deliberate self-poisoning should be explored, since most drug-induced seizures in this age group resulted from intentional ingestion.